Accessory minerals of kanevsko-buchaksky deposits in the arched part of voronezh antecline on the territory of sheet M-37-XI (Bobrov) (Proceedings of Voronezh State University. Series: Geology, 2018)
Accessory minerals of Kanevsko-Buchaksky deposits in four reference sections on the territory of M-37-XI sheet (Voronezh region) are considered. These sections are composed of sands of finegrained, predominantly sorted, with the exception of the so-called cut. 191, where they are heterogeneous. The light fraction of sands consists of grains of quartz, glauconite from the first to 15%, feldspars up to 9% and clay constituents, on average, from 0,5 to 3, less often up to 10%. The heavy fraction from the first fraction to 0,5%, and its lycoxene-zircon-ilmenite association with an admixture of other minerals. The results of granulometric and mineralogical-petrographic study of Kanev-Buchak sands showed that the formation of sands occurred in a shallow-water basin with a heterogeneous bottom morphology under conditions of various hydrodynamic regimes. The low content and composition of the heavy fraction does not allow a positive assessment of prospects for reasonable areas.
Keywords: Paleogene; Kanev-Buchak deposits; accessory minerals; granulometric analysis; heavy fraction